2017
DOI: 10.26714/jk.6.1.2017.56-62
|View full text |Cite
|
Sign up to set email alerts
|

Status Kesehatan Dan Keteraturan Pemanfaatan Layanan Infertilitas

Abstract: ABSTRAK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
2
1
Order By: Relevance
“…Moreover, the result of statistical tests indicated that there was no significant correlation between health status and health care service utilization at the Outpatient Unit of Haji General Hospital with p-value of0.621. This result was contrary to the result of recent research conducted by Rohmah (2017), which stated that, statistically, health status had a significant correlation to the regular health care service utilization. The excellent health status would reduce the regular service utilization.…”
Section: The Correlation Between Health Status and Health Care Serviccontrasting
confidence: 99%
“…Moreover, the result of statistical tests indicated that there was no significant correlation between health status and health care service utilization at the Outpatient Unit of Haji General Hospital with p-value of0.621. This result was contrary to the result of recent research conducted by Rohmah (2017), which stated that, statistically, health status had a significant correlation to the regular health care service utilization. The excellent health status would reduce the regular service utilization.…”
Section: The Correlation Between Health Status and Health Care Serviccontrasting
confidence: 99%
“…achievement number on giving exclusive breastfeed which gives impact to the quality of live on the next generation and on national economy (Rohmah et al, 2022).…”
Section: Article Infomentioning
confidence: 99%
“…Even if an infertile couple realizes these shortcomings and seeks medical help, the journey they have to take is also not straightforward. The lack of information regarding the medical treatment of infertility also results in the tendency of Indonesians to seek alternative traditional medicine, which is sometimes illogical but believed to cure their infertility (Rohmah, 2017).…”
Section: Introductionmentioning
confidence: 99%